Students’ and Teachers’ Opinions about the Effect of Integrating Asynchronous E-learning on Students’ Motivation in English Language Classrooms - BENHARA, Amina; Ghouar, Amor (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
Over the recent years, it has been noticed that the new generations of learners are growing up with technology, which becomes a natural and integrated part of their lives. Technology has marked a significant role in facilitating the process of learning. It gives learners exposure to knowledge and the opportunity to practise it. In a narrow scope, the field of learning EFL has also adopted technology around for decades. This last helped to solve many educational problems in foreign language classrooms. Despite the widespread recognition of the importance of integrating modern technology in learning language classes, its use is still absent in the Algerian schools and universities. The present research paper reports a conducted study that endeavors to examine the students' and teachers 'opinions about the effect of integrating asynchronous e-learning as a contemporary technological element on learners of English motivation. The study adopts a descriptive research method through administering two questionnaires for teachers and learners of Banta 2 English department. The findings represent that both teachers and learners support the idea of using asynchronous e-learning as a remedial technique to provoke learners’ positive educational motivation.